Thoracoscopic right anterior basal segmentectomy with unique anatomic variation: a case report and literature review - Liu, Tiancheng; Huang, Sishi; Zhang, Jianbin; Jin, Lili; Shen, Qibin (Frontiers in Oncology, 2025)
BackgroundAnatomic basal segmentectomy is often regarded as a complex procedure, particularly in the presence of complex anatomical variations.Case reportHerein, we present a case of a 55-year-old female patient diagnosed with invasive lung adenocarcinoma. Three-dimensional computed tomography bronchography and angiography (3D-CTBA) displayed a unique combined variation in the basal segment of right lower lobe (RLL): The medial basal subsegmental bronchi (BX7a+BX7t) originated from both the anterior and posterior segmental bronchi; The medial basal subsegmental arteries emanated from the anterior and posterior basal segmental arteries; The medial anterior segmental vein shared a trunk with both the anterior basal and lateral basal subsegmental veins. With precise preoperative planning, thoracoscopic anterior basal segmentectomy was successfully executed.ConclusionThis case again highlights the importance of 3D-reconstruction in pulmonary segmentectomy. Detailed understanding of anatomic features of segmental bronchi and vessels is imperative for those with complex anatomical variations.